2001
DOI: 10.1128/mcb.21.12.4016-4031.2001
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor-Induced Tumor Cell Invasion and Metastasis Initiated by Dephosphorylation and Downregulation of Focal Adhesion Kinase

Abstract: Upregulated epidermal growth factor (EGF) receptor (EGFR) expression and EGFR-induced signaling havebeen correlated with progression to invasion and metastasis in a wide variety of carcinomas, but the mechanism behind this is not well understood. We show here that, in various human carcinoma cells that overexpress EGFR, EGF treatment induced rapid tyrosine dephosphorylation of focal adhesion kinase (FAK) associated with downregulation of its kinase activity. The downregulation of FAK activity was both required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
253
3
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(279 citation statements)
references
References 83 publications
(90 reference statements)
19
253
3
4
Order By: Relevance
“…These findings do not exclude the possibility that other signaling molecules such as FAK are also involved in the EGFR-Etk activation. For instance, FAK could form complexes with EGFR in the absence of EGF in A431 cells (Lu et al, 2001). David et al (Sieg et al, 2000) have demonstrated that FAK forms a complex with the activated EGFR and is required for EGF-stimulated cell motility.…”
Section: Discussionmentioning
confidence: 99%
“…These findings do not exclude the possibility that other signaling molecules such as FAK are also involved in the EGFR-Etk activation. For instance, FAK could form complexes with EGFR in the absence of EGF in A431 cells (Lu et al, 2001). David et al (Sieg et al, 2000) have demonstrated that FAK forms a complex with the activated EGFR and is required for EGF-stimulated cell motility.…”
Section: Discussionmentioning
confidence: 99%
“…FAK is a major protein of the focal adhesion complex, playing a key role in cell migration and matrix survival signals (19,20). FAK is activated by numerous growth factors, including ErbB ligands epidermal growth factor (21,22) and heregulin (23), followed by integrin clustering in response to components present in the extracellular cell matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence indicates that collaborative pathways derived from these two signals are crucial in regulating a range of cell activities, such as proliferation, differentiation, apoptosis, adhesion, and migration [93][94][95][96].…”
Section: Versican Interaction With Epidermal Growth Factor Receptor (mentioning
confidence: 99%